2022
DOI: 10.3390/cancers14215386
|View full text |Cite
|
Sign up to set email alerts
|

Tau Protein as Therapeutic Target for Cancer? Focus on Glioblastoma

Abstract: Despite being extensively studied for several decades, the microtubule-associated protein Tau has not finished revealing its secrets. For long, Tau has been known for its ability to promote microtubule assembly. A less known feature of Tau is its capability to bind to cancer-related protein kinases, suggesting a possible role of Tau in modulating microtubule-independent cellular pathways that are associated with oncogenesis. With the intention of finding new therapeutic targets for cancer, it appears essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 323 publications
(369 reference statements)
0
7
0
Order By: Relevance
“…Although microglia cells can ingest NFTs, they do so inefficiently and may release tau aggregates into the environment, propagating disease pathology ( Hopp et al, 2018 ; Perea et al, 2018 ). The functionality of tau protein in brain pathologies is not only limited to AD; its role in GBM is also documented ( Pagano et al, 2021 ; Hedna et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although microglia cells can ingest NFTs, they do so inefficiently and may release tau aggregates into the environment, propagating disease pathology ( Hopp et al, 2018 ; Perea et al, 2018 ). The functionality of tau protein in brain pathologies is not only limited to AD; its role in GBM is also documented ( Pagano et al, 2021 ; Hedna et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has explored the interplay between autophagy and MAPT in AD and has demonstrated that overexpression of MAPT /tau inhibits the fusion of autophagosomes with lysosomes, leading to autophagosome accumulation through increased levels of LC3 protein [ 54 ]. Although direct links between MAPT and autophagy in cancer remain limited, the high expression levels of Tau protein in glioblastoma, a tumor with enhanced autophagy activity, have raised questions about its possible role in oncogenesis and its implications for cancer therapy [ 55 ].…”
Section: Clustering Solid Tumors Based On Autophagy-related Genesmentioning
confidence: 99%
“…Additionally, we recently demonstrated that Tau contributes significantly to the invasiveness and proliferation of GBM-derived U87 cells [20,21]. We further argued that Tau protein could represent a new interesting anticancer target in GBM [22]. Interestingly, molecules developed for Tau-related neurodegenerative diseases could display anticancer potency, especially compounds containing the thiazole group (see review of [23]).…”
Section: Introductionmentioning
confidence: 99%